The personality profile of borderline personality disordered patients using the five-factor model of personality - Sabrina Verardi (International Journal of Clinical and Health Psychology, 2008)
The purpose of this ex post facto study is to analyze the personality profile of outpatients who met criteria for borderline personality disorder according to the Five-Factor Model of personality. All patients (N = 52) completed the International Personality Disorder Examination (IPDE) Screening Questionnaire, the Big Five Questionnaire (BFQ), the Beck Depression Inventory (BDI), and the Beck Hopelessness Scale (BHS). The results show a high comorbidity with other DSM-IV-TR Axis II disorders, in particular with those from Cluster C. The BFQ average score indicates that the outpatients who met borderline criteria score lower than controls on all five dimensions, and especially on emotional stability. Correlations were computed between the BFQ and the IPDE scales in our sample. These results suggest that specific personality profile are linked to different comorbidity patterns. More than a half of our sample has clinically significant scores on Beck's scales. Surprisingly, depression and hopelessness are neither correlated with the borderline scale, nor have an effect in the relationship between personality and personality disorders.